Evaluation of Children Who Swallowed Safety Pins - Deveci, Uğur; Doğan, Yaşar; Kayaokay, Abdullah Murat; Akgeyik, Şükran; Karakoç, Ferhat; Çınar, Muhammed Ali (Northwestern University Press, 2024)
Introduction: Cases of swallowed safety pins are often observed in Turkey because of the tradition of pinning a blue eye bead on children to ward against evil. This study aimed to evaluate the diagnosis, endoscopic management, and long-term follow-up of children who were admitted to our hospital with a complaint of swallowing safety pins. Methods: A retrospective evaluation was made of the clinical characteristics of 47 pediatric patients who were treated because of a swallowed safety pin between 2010 and 2022 in a tertiary level healthcare center. Results: The cases comprised 24 (51.1%) females and 23 (48.9%) males with a median age of 10 months (range, 5 months-15 years). The median age of the females was observed to be approximately 5 months older than that of males (p<0.003). Of the total sample, 40 (85%) infants were breastfed. In all cases, the foreign body had been swallowed by accident. The majority of the cases (n=25, 53.2%) were resident in the province where the hospital is located, and the other cases presented from surrounding provinces. The localization of the swallowed safety pin in the gastrointestinal system was observed in the stomach (n=26, 65.3%), first esophageal stricture (n=10, 21.3%), second esophageal stricture (n=6, 12.8%), third esophageal stricture (n=2, 4.2%), duodenum (n=3, 6.4%), and cecum (n=3, 6.4%). The safety pin was removed endoscopically in 31 (66%) cases. In 2 cases, the safety pin was observed to be lodged in the duodenum. Of the pins removed, the end was open in 25. In 15 cases, as the safety pin was seen to be closed, it was left for spontaneous elimination. Surgery was required in 1 case because the safety pin was embedded in the cecum. No complications were observed in any patient during or after the procedures. Conclusion: The swallowing of safety pins is frequently observed, especially in the breastfeeding period of infants. In most cases, safety pins can be safely removed using an endoscopic method without complications. © Copyright 2024 by Society of Pediatric Emergency and Intensive Care Medicine Journal of Pediatric Emergency and Pediatric Intensive Care published by Galenos Yayınevi.
Çengelli İğne Yutan Çocukların Değerlendirmesi
Keywords: child; endoscopy; Foreign body ingestion; safety pin